2023
DOI: 10.1002/fsn3.3532
|View full text |Cite
|
Sign up to set email alerts
|

The internal aqueous phase gelation improves the viability of probiotic cells in a double water/oil/water emulsion system

Abstract: This research studied the viability of probiotic bacterium Lactobacillus plantarum (L. plantarum) encapsulated in the internal aqueous phase (W1) of a water‐in‐oil‐in‐water (W1/O/W2) emulsion system, with the help of gelation and different gelling agents. Additionally, the physicochemical, rheological, and microstructural properties of the fabricated emulsion systems were assessed over time under the effect of W1 gelation. The average droplet size and zeta potential of the control system and the systems fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…The storage stability of the encapsulated cells in DE after 42 days of storage at 37 • C indicated a gradual decrease in the cells until the 21st day and then a sharp decrease until the end of storage (survival rates of about 95% and 62% in the 7th and 42nd days of storage were reported, respectively) [59]. Abbasi, et al [60] investigated the viability of L. plantarum encapsulated in the inner phase of a W 1 /O/W 2 DE under the effects of heating and pH in the presence of various gelling agents (gelatin, alginate, tragacanth gum, and carrageenan) in W 2 . They reported that the initial count of free cells (9.95 log CFU/mL) reached 9.97, 8.10, 6.37, and 0 log CFU/mL after 2 min of heating at 30, 50, 63, and 72 • C, respectively.…”
Section: Improved Viability Of Probioticsmentioning
confidence: 97%
“…The storage stability of the encapsulated cells in DE after 42 days of storage at 37 • C indicated a gradual decrease in the cells until the 21st day and then a sharp decrease until the end of storage (survival rates of about 95% and 62% in the 7th and 42nd days of storage were reported, respectively) [59]. Abbasi, et al [60] investigated the viability of L. plantarum encapsulated in the inner phase of a W 1 /O/W 2 DE under the effects of heating and pH in the presence of various gelling agents (gelatin, alginate, tragacanth gum, and carrageenan) in W 2 . They reported that the initial count of free cells (9.95 log CFU/mL) reached 9.97, 8.10, 6.37, and 0 log CFU/mL after 2 min of heating at 30, 50, 63, and 72 • C, respectively.…”
Section: Improved Viability Of Probioticsmentioning
confidence: 97%